2013
DOI: 10.1021/ef301859s
|View full text |Cite
|
Sign up to set email alerts
|

A USANS/SANS Study of the Accessibility of Pores in the Barnett Shale to Methane and Water

Abstract: Shale is an increasingly important source of natural gas in the United States. The gas is held in fine pores that need to be accessed by horizontal drilling and hydrofracturing techniques. Understanding the nature of the pores may provide clues to making gas extraction more efficient. We have investigated two Mississippian Barnett Shale samples, combining small-angle neutron scattering (SANS) and ultrasmall-angle neutron scattering (USANS) to determine the pore size distribution of the shale over the size rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
155
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(164 citation statements)
references
References 25 publications
8
155
1
Order By: Relevance
“…Within the phyllosilicates group, illiterich mixed layer illite-smectite is the most prominent component, followed by kaolinite, illite, muscovite and chlorite. In addition, there is a moderate content of quartz (8)(9)(10)(11)(12)(13)(14)(15)(16) wt.%) and minor contents of pyrite (4-9 wt.%), feldspars (1-5 wt.%) and dolomite (0.3-6.4 wt.%).…”
Section: Mineralogymentioning
confidence: 99%
See 1 more Smart Citation
“…Within the phyllosilicates group, illiterich mixed layer illite-smectite is the most prominent component, followed by kaolinite, illite, muscovite and chlorite. In addition, there is a moderate content of quartz (8)(9)(10)(11)(12)(13)(14)(15)(16) wt.%) and minor contents of pyrite (4-9 wt.%), feldspars (1-5 wt.%) and dolomite (0.3-6.4 wt.%).…”
Section: Mineralogymentioning
confidence: 99%
“…Ultra small angle neutron scattering and small angle neutron scattering techniques are also useful for the determination of pore connectivity in shales. [8][9][10] Sorbed gas in shale is in equilibrium with the homogeneous bulk gas phase ("free gas") in larger pores. Sorption capacity depends on pressure and temperature, and structural characteristics, such as (micro-) pore volume and organic matter type, maturity and content.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the interrelation between the pore morphology, sorption characteristics, and potential gas storage capacities of organic-rich shales is important because of the discovered significant gas contents of shale gas reservoirs. The developed new technologies of hydrocarbon extraction from low-permeability, unconventional-type reservoirs utilizing hydrofracturing and horizontal drilling stimulated a significant increase in research in this area [81].…”
mentioning
confidence: 99%
“…Recently initiated SANS/USANS studies demonstrated high effectiveness of these techniques for characterizing the morphology of dry and wet shales, and providing information on their accessible and closed porosity as a function of pore size (Fig. 10.38, [81][82][83]). …”
mentioning
confidence: 99%
“…Desbois et al, 2009;Heath et al, 2011;Klaver et al, 2012;Clarkson et al, 2012Clarkson et al, , 2013Ruppert et al, 2013;Yang et al, 2014), e.g. in pressure shadows or at the interfaces of clay aggregates.…”
Section: Mudstone Grain and Pore-size Distributionsmentioning
confidence: 99%